Evaluasi Kebijakan Sistem Pembayaran Non Tunai Di Gerbang Tol Sentul Utara Ruas Jagorawi - Nandhyfa Desra Syafira (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
Toll road users often complain about congestion problems that occur at entrance toll gates and exit toll gates due to the queue of toll road users in paying tickets using cash takes a long time, queues of congestion on toll roads cause losses for consumers in the form of wasted time, energy and vehicle fuel. This study aims to determine the results of the evaluation of the non-cash payment system policy at the North Sentul toll gate of Jagorawi Section. This research is a descriptive research using qualitative methods. The collection of 10 informants using Non Probabilita sampling techniques, the type is judgment sampling. Data were collected by triangulation techniques, namely observation, interviews and documentation. The informants in the study were North Sentul toll road users and North Sentul toll gate employees. Based on the results of research on the evaluation of cashless payment system policies at the North Sentul toll gate, it has not been able to overcome the existing problems. This cashless payment system policy is effective because it is considered safe, convenient and fast. However, on the other hand, this policy is said to be still ineffective because rider machines or payment machines often occur human errors while technicians to repair the machine are not standby